Sugar cane yeast (Saccharomyces cerevisiae) in diets for Nile tilapia - Lima, Misleni Ricarte de; Ludke, Maria do Carmo Mohaupt Marques; Santos, Elton Lima; Oliveira, Cláudio José Parro de (Revista de Ciências Agroveterinárias, 2024)
The research was conducted to evaluate the use of sugar cane yeast (Saccharomyces cerevisiae) dehydrated by the spray dryer method in the diets of Nile tilapia. We used 144 fingerlings with average initial weight 3.6 ± 0.03 g, distributed in 24 tanks with a capacity of 80L, connected to a recirculating water system, using a biological filter for the mineralization of ammonia to nitrite, and nitrite to nitrate, and a continuous aeration system. The experimental design was completely randomized design consisting of four treatments (0.00, 10.00, 20.00 and 30.00% inclusion of yeast) and six repetitions. The experiment last 60 days and was evaluated the final weight, total length, survival rate, weight gain, feed intake, apparent feed conversion, protein efficiency rate, carcass yield, hepatosomatic and liposomatic index. Regarding the analyzed parameters, no significant effect was observed for total length, feed intake, feed conversion, protein efficiency rate, carcass yield, hepatosomatic and liposomatic index. However, the final weight and weight gain showed a quadratic effect, with the best level of yeast inclusion indicated by the regression for these parameters were 2.26 and 3.04%, respectively. As for the survival rate of the animals, a linear increase was observed. Based on the results obtained, the inclusion of 3.04% of yeast for Nile tilapia fingerlings is recommended.